IgG4-related disease: an analysis of the clinicopathological spectrum: UK centre experience. Issue 1 (19th August 2021) - Dassanayaka, Wajira; Liyanaarachchi, Kanchana Sanjeewani; Ala, Aftab; Bagwan, Izhar N
Abstract : Aim: To retrospectively evaluate the characteristic clinicopathological spectrum in patients with suspicion of IgG4-related disease (IgG4RD). Methods: Winpath histology database from January 2011 to April 2018 identified all suspected IgG4RD cases wherein IgG4 immunohistochemistry was performed. The histology slides were reviewed to categorise cases into Boston criteria groups—highly suggestive of IgG4RD, probable IgG4RD and insufficient evidence. Information regarding clinical data, treatment received, follow-up and serum IgG4 levels was obtained from medical records and AllScripts Patient Administration System (APAS) clinical database. Results: The study included 204 patients and the most common sites of biopsy/resection were pancreas and duodenum. The most common clinical presentation was fibroinflammatory lesion or mass/lump. On histology, 54/204 (26.47%) cases showed typical storiform fibrosis, 65/204 (32.64%) had >10 IgG4+ plasma cells per high power field and only one case showed thrombophlebitis (0.49%). There were 14/204 (6.78%) cases categorised as highly suggestive of IgG4RD; 8 of these showed high serum IgG4 levels and were managed clinically as true IgG4RD. Conclusion: Histological diagnosis of IgG4RD remains challenging, as not all characteristic features are always present especially in small biopsies. Due to the novelty of its experience, fear of over diagnosis in the context of malignancy and features overlapping with diseases of similar clinical scenario, diagnosis of IgG4RD has become more puzzling. Further multicentre clinical trials/studies are advisable.